THE STRUCTURAL FORMS OF COMPLEX SUBORDINATE CLAUSES - Bakirova Elnora Anvarovna (Web of Journals Publishing, 2025)
The article is devoted to the analysis of the structure of complex subordinate clauses expressing possessive relations in the Uzbek language, with an emphasis on their interpretation based on linguistic evidence.
Keywords: Сomplex subordinate clauses, compound sentences with coordinative relations, compound sentences with subordinative relations, and compound sentences with mixed syntactic relations.